Impact of Environmental Tobacco Smoke on Pulmonary Functions of Females - Sadaf Zia; Hamid Shafiq; Fouzia Jamshed; Rana Muhammad Tahir Salam (Aziz Fatimah Medical and Dental College, 2019)
Background: Environmental tobacco smoke (ETS) or passive smoking has an emerging burden on the society thus affecting the quality of individual's life. According to World Health Organization ETS is referred to the involuntary inhalation of burning tobacco products emitted from the smoking devices. More than 4000 harmful compounds including carcinogens are emitted from burning cigarettes and cigars etc, which are extremely harmful for human health. Pakistan has high tobacco consumption. Due to this reason women and children are frequently exposed to indoor ETS. Subjects with exposure to ETS have same ill effects as light active smokers. Aim: To evaluate the lung functions of passive smokers and to compare with non-smokers of the same age and social background. Methods: The study was conducted in a private hospital of Faisalabad. 250 female subjects aged 15- 45 years were included in the study. Data was collected by specially designed structured proforma  and lung Function tests were performed by spirometry. Data was analyzed by using SPSS 20 version. P value ? 0.05 was taken as significant. Results: 250 females participated in study. 61.2 % of total study population was exposed to tobacco smoking. Out of total 250 subjects, 155(62%) had undiagnosed airway obstruction. FEV1, FVC and FEV1/ FVC ratio were lower in passive smokers as compared to non- smokers. Significant difference was found in FEV1 (0.003*), FVC (P value 0.002*), FEV1/FVC (0.001*). FEV1/FVC ratio of < 0.70 was noted in 89.5% and 18.5% of total passive smokers and nonsmokers respectively (obstructive air way pattern). 55% of subjects with reduced lung function parameters also reported chronic cough and shortness of breath. Conclusion: Airway obstruction was found among majority of passive smokers, confirmed by reduced lung function test.